(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2024)
The emotion of shame in the Arab context is culturally specific and viewed in a shame-honour paradigm. The interdisciplinary study here unpacks the Jordanian sociopolitical issues which are embedded within the cultural concept of shaming using a critical metaphor method. The study on selected 97 online editorials written by Ahmad Hasan al-Zu’bi here reveals a metaphoric bipolarisation technique which conjures the notions of shame on Arab’s sociopolitical submissiveness to global powers but argues that the global powers’ domination is a myth. These claims communicated by the dual metaphors provoke the most intense shame emotion as they violate the Arab tradition and honour. They are intended at awakening the people from their own powerlessness due to internal squabbling and corrupt leadership as well as hegemony of external powers. From the perspective of political communication in the digital age, they echo both nationalistic and populist intentions through the dichotomous shame-pride cultural paradigm. Generally, this study demonstrates that the use of these journalistic rhetorical moves which are rooted in a shame herd culture is a distinctive tactical communication capable of foregrounding an emancipatory agenda in restoring the honour of any sociopolitically affected community.